IMPLEMENTASI KOMPETENSI PEDAGOGIK GURU TERHADAP PERILAKU SOSIAL ANAK USIA DINI DI TK ABA 1 KALIWATES - Neilaturrahma,; Khoiriyah,; Nuraini Kusumaningtyas, (Jurnal Cakrawala Ilmiah, 2024)
Pedagogical competency is very important because it is a competency for managing student learning. The social behavior in question is the social behavior of self-confidence and cooperation. The research problem to be solved is through the implementation of teacher pedagogical competence on the behavior of children aged 5 to 6 years at TK ABA 1 Kaliwates.The research aims to determine the pedagogical competence of teachers regarding the social behavior of children aged 5–6 years at TK ABA 1 Kaliwates. This research was carried out at the TK Aisyiyah Bustanul Athfal 1 Kaliwates for the 2023-22024 academic year. The type of research used was descriptive-qualitative; the data collection techniques used in this research were observation, interviews, and documentation. The research subjects were group B teachers who were certified as teachers, driving teachers, and had additional duties as deputy principals for the curriculum department. The results of the research can be concluded that teachers' pedagogical competence is able to develop social behavior in early childhood using strategies of providing opportunities, providing motivation, providing rewards, as well as using positive models for children as teachers' efforts to develop self-confident attitudes. Furthermore, teachers can develop social behavior in early childhood, an attitude of cooperation, with family role-playing project activity strategies.